Parasites, Bacteria and Viruses of the Edible Dormouse Glis glis (Rodentia: Gliridae) in the Western Palaearctic - Alexander A. Kirillov; Nadezhda Yu. Kirillova; Alexander B. Ruchin (Diversity, 2022)
An overview of the parasites, bacteria and viruses of Glis glis (Rodentia, Gliridae) inhabiting the Western Palearctic is given. A total of 85 articles published from 1895 to 2021 were reviewed and analysed in our study. According to the literature’s data, 104 species associated with G. glis are recorded: 4 viruses, 8 Protozoa, 6 Cestoda, 6 Trematoda, 4 Nematoda, 1 Heteroptera, 2 Anoplura, 39 Siphonaptera and 34 Acari. The most studied group is ectoparasites. To a lesser extent, parasitic worms in G. glis were studied. There is very little data about the dormouse protozoans and viruses. The most studied parasites, viruses and protozoans of G. glis are in Germany, where 21 species were noted. The largest number of parasites was found in the dormouse in Russia (22), but of two groups only: helminths and ectoparasites. Only 20 out of 104 parasite species recorded in G. glis are host-specific. Most parasites (60 species) found in G. glis have a Palaearctic and cosmopolitan distribution. Three viruses, six species of protozoa and three helminths have veterinary and medical significance as potential pathogens of dangerous zoonoses. Also, many species of fleas, mites and ticks found on G. glis are vectors of a number of dangerous vector-borne diseases in humans and domestic and wild animals.